The Role of Parents in Blended Learning Towards Student Character Values in The Covid-19 Pandemic - Lestaria Simvony, Yusnita; Budi Santosa, Agus; nugroho, wahyu (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The Covid-19 pandemic hampers the cultivation of character values ​​in students, therefore it is necessary for the role of parents in Blended Learning to instill character values. This research is a quantitative research with sampling technique using stratified proportional random sampling. The results of the Shapiro-Wilk normality test showed that the significance value of the parent's role was 0.157 > 0.05. The significance value for the student character is 0.280 > 0.05 so that the data is normally distributed. Test for linearity sig 0.305 > 0.05 so that the variables X and Y are linear. The results of the hypothesis test are 0.000 <0.05, and the Pearson Correlation value is 0.600, then Ha is accepted and H0 is rejected. So it can be concluded that there is a strong relationship between the role of parents in blended learning and the cultivation of character values ​​during the Covid-19 pandemic.